Controllable fabrication of CuO nanostructure by hydrothermal method and its properties - Jiang, Tingting; Wang, Yongqian; Meng, Dawei; Wu, Xiuling; Wang, Junxia; Chen, Jieyu (Applied surface science, 2014)
The general morphologies of the synthesized CuO products prepared by hydrothermal route at different reactant concentration were analyzed by FESEM and results are shown in Fig. 2. With the increase of the Cu(CH3COO)2 concentration, the morphology of CuO nanostructure has a large change. The morphology of flower-like CuO nanostructures is obtained at 0.4M/L, as shown in Fig. 2a, which indicates that the flower-like CuO nanostructures are composted of the irregular nanosheets with about 70nm in width and 1.7μm in length. With the reactant concentration increasing, the morphology of flower-like CuO nanostructures disappeared and dispersed plume-like nanosheets formed, as shown in Fig. 2b. The size of nanoplates is about 400nm in width and 900nm in length. When the reactant concentration is equivalent to 0.6M/L, the morphology transformed into spindle-like nanostructure. So, the morphology of CuO nanocrystals can be controlled by changing reactant concentration. •Reactant concentration is the main factor to control the morphology of CuO nanostructure.•Both hydrothermal temperature and time have great influence on the crystallinity of CuO nanocrystals.•The growth mechanism for the formation of CuO nanostructure is reasonable and its schematic representation is clear and concise.•The photo-degradation rate of methylene blue with CuO nanoparticles can reach 92.1% which is almost two times than that of CuO powder with general size. The copper oxide (CuO) nanostructures of varying shape were synthesized by a simple hydrothermal method without using any template and surfactants. The influences of reactant concentration, hydrothermal temperature and time on the growth of nanostructure were investigated. And the samples were characterized by means of scanning electron microscope (FESEM) and X-ray powder diffraction (XRD). At the same time, photo-decomposition test and UV–vis spectroscopy were done. The results shows that the CuO nanostructure has monoclinic structure with single crystalline phase. However, the structure and morphology of CuO nanocrystal can be controlled by changing reactant concentration. Its photo-degradation rate to methylene blue can reach 92.1%. And the optical band gap calculated of nanosheets is found about 5.89eV. Moreover, the plausible growth mechanism for the formation of CuO nanostructure is proposed.